2013
DOI: 10.1111/ajr.12009
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social support, lifestyle and functional disability on psychological distress in rural China: Structural equation modelling

Abstract: A third of the rural population in China reported psychological distress, with the highest prevalence observed in women. Functional disability had a significant direct effect, social support had significant indirect effects and lifestyle had both significant direct and indirect effects on psychological distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…However, more researchers have used ≥16 as the cut‐off point. Even utilizing this cut‐off point, the prevalence of this study is much higher than that found in the general population in rural areas of China (32.9%) (Feng, Ji, & Xu, ), among pulmonary tuberculosis patients in China (58.6%) (Feng & Xu, ) and in South Africa (81%) (Peltzer, Naidoo, & Matseke, ). This prevalence is comparable to those of Chinese telephone operators who are under extreme pressure (91.8%) (Tian, Sun, Zou, Liu, & Li, ).…”
Section: Discussionmentioning
confidence: 53%
“…However, more researchers have used ≥16 as the cut‐off point. Even utilizing this cut‐off point, the prevalence of this study is much higher than that found in the general population in rural areas of China (32.9%) (Feng, Ji, & Xu, ), among pulmonary tuberculosis patients in China (58.6%) (Feng & Xu, ) and in South Africa (81%) (Peltzer, Naidoo, & Matseke, ). This prevalence is comparable to those of Chinese telephone operators who are under extreme pressure (91.8%) (Tian, Sun, Zou, Liu, & Li, ).…”
Section: Discussionmentioning
confidence: 53%
“…The relationship between the amount of physical activity and social support shows that humans are more likely to pursue a healthy lifestyle when social support increases [23,24]. Social support refers to support received from others.…”
Section: The Relationship Between Physical Activity Aging Anxiety Amentioning
confidence: 99%
“…In the present research, the prevalence of psychological distress among rural residents from Anhui Province was 33.4%, which is slightly higher than that (33%) of the rural residents in Shangdong Province, China and that (31%) in rural communities in Australia [ 50 , 51 ]. Earlier literature showed that the rates of psychological distress for famers and non-farmers in rural China were 31.13% and 30.01%, respectively [ 52 ].…”
Section: Discussionmentioning
confidence: 51%